Evidence of evaluation and interventions for self-care of patients with heart failure (Research, Society and Development, 2020)
Introduction: Heart failure is a serious chronic disease, with high morbidity and mortality, which brings limitations in daily life. Therefore, there is relevance of nursing actions to promote self-care for patients with heart failure. Objective: To analyze the scientific evidence on self-care assessment and the proposed non-pharmacological interventions in patients with heart failure. Method: This is an integrative review in databases carried out from March to April 2018. And for that, 24 articles were published in full, published between 2008 and 2018, referring to scales for measuring self-care of patients with impairment. cardiac. Conclusion: Above all, there was a diversity of interventions capable of supporting the improvement of the self-care behavior evaluated in patients with heart failure, whether under home, outpatient and hospital treatment.